2009
DOI: 10.1126/science.1180906
|View full text |Cite
|
Sign up to set email alerts
|

Global Observations of the Interstellar Interaction from the Interstellar Boundary Explorer (IBEX)

Abstract: The Sun moves through the local interstellar medium, continuously emitting ionized, supersonic solar wind plasma and carving out a cavity in interstellar space called the heliosphere. The recently launched Interstellar Boundary Explorer (IBEX) spacecraft has completed its first all-sky maps of the interstellar interaction at the edge of the heliosphere by imaging energetic neutral atoms (ENAs) emanating from this region. We found a bright ribbon of ENA emission, unpredicted by prior models or theories, that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
570
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 483 publications
(591 citation statements)
references
References 30 publications
(39 reference statements)
19
570
1
1
Order By: Relevance
“…This implies that HSTOF can observe a different dependence on direction of the hydrogen ENA flux than the lower energy instruments INCA (highest energy channel ∼46 keV: Krimigis et al 2009) and IBEX (E ≤ 6 keV: McComas et al 2009) The result is not substantially changed by taking adiabatic acceleration, diffusion and escape processes into account. Our preliminary result (Czechowski et al 2006b), which suggested a strong diffusion effect, was affected by the error in calculating the adiabatic acceleration (see the remark in Sect.…”
Section: Results From the Model: The Ena Fluxesmentioning
confidence: 97%
“…This implies that HSTOF can observe a different dependence on direction of the hydrogen ENA flux than the lower energy instruments INCA (highest energy channel ∼46 keV: Krimigis et al 2009) and IBEX (E ≤ 6 keV: McComas et al 2009) The result is not substantially changed by taking adiabatic acceleration, diffusion and escape processes into account. Our preliminary result (Czechowski et al 2006b), which suggested a strong diffusion effect, was affected by the error in calculating the adiabatic acceleration (see the remark in Sect.…”
Section: Results From the Model: The Ena Fluxesmentioning
confidence: 97%
“…Recently, our understanding of the boundaries of the heliosphere and its interaction with the LISM has been expanded by the unexpected results of the Interstellar Boundary EXplorer (IBEX) and the in situ observations by the Voyager spacecraft (Stone et al 2005). Among the findings is the IBEX ribbon (McComas et al 2009), which provides insight into the interstellar magnetic field. Another key component of the interaction is the interstellar flow vector, u LISM , which denotes the relative motion between the Sun and the LISM.…”
Section: Contextmentioning
confidence: 99%
“…Details of both statistical smoothing as we apply it to TWINS data and the background suppression procedure are provided in McComas et al [2012, Appendix A]. This technique that produces statistically smoothed images has also been applied successfully to the ENA measurements on IBEX [McComas et al, 2009b].…”
Section: Twins Ena Instrumentsmentioning
confidence: 99%